ChemInform Abstract: Single Crystal X‐Ray Structure of Cu3TaSe4 and a Comparative Study of Cu3MX4 (M: V, Nb, Ta; X: S, Se, Te). Issue 24 (2nd June 2014) - Ali, Sk Imran; van Smaalen, Sander
Abstract Single crystals of Cu3TaSe4 are obtained from a precursor that is produced by chemical vapor reaction of Cu, Ta, and Se in a molar ratio of 0.21:1.15:2 (quartz ampoule in two‐zone furnace, 1.